Unveiling the Antibacterial Activity of Petai Seed Ethanol Extract (Parkia speciosa Hassk) with the Kirby-Bauer Method - Alioes, Yustini; Efendi, Altio; Ramadhan, Mario Arya (Faculty of Medicine, Universitas Andalas, 2024)
The increasing number of antibiotic resistance cases have to seek alternative treatments, including the petai plant (Parkia speciosa Hassk). Petai seeds primarily contain chemical compounds such as tannins, saponins, alkaloids, and flavonoids, which are known for their antibacterial properties. Objective: To determined the antibacterial activity of petai seed ethanol extract (P. speciosa Hassk) against Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella typhi. Methods: This experiment used the Kirby-Bauer Method. Petai seeds were extracted with ethanol using maceration techniques, and the viscous extract was dissolved into concentrations of 25%, 50%, 75%, and 100%. Screening paper soaked in the extract was placed on agar plates inoculated with the test bacteria, and the plates were incubated for 24 hours. The inhibition zones were measured with a caliper, and the data were analyzed statistically. Results: The study found that the ethanol extract of petai seeds exhibited moderate antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa and weak antibacterial activity against Salmonella typhi. Conclusion: Increasing the concentration of the extract significantly enhanced its antibacterial effect against Staphylococcus aureus and Pseudomonas aeruginosa, indicating that petai seed ethanol extract could be a potential alternative treatment for bacterial infections.Keywords: Â antibacterial, extract ethanol, Kirby-Bauer method, petai seed